2021
DOI: 10.1002/gea.21853
|View full text |Cite
|
Sign up to set email alerts
|

Carbonates from the ancient world's longest aqueduct: A testament of Byzantine water management

Abstract: The fourth‐ and fifth‐century aqueduct system of Constantinople is, at 426 km, the longest water supply line of the ancient world. Carbonate deposits i659ide an archive of both archaeological developments and palaeo‐environmental conditions during the depositional period. The 246‐km‐long aqueduct line from the fourth century used springs from a small aquifer, whereas a 180‐km‐long fifth‐century extension to the west tapped a larger aquifer. Although historical records testify at least 700 years of aqueduct act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 33 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…In aqueduct channel sections that are steep and where no daylight penetrates, deposits are usually sparitic and dense due to fast water flow and reduced biological activity, while gently dipping sections, with slow water flow or sections where light is admitted to the channel, tend to be dominated by more micritic and porous deposits (Figures 2a‐X,XI, 4e and 5d) (Kessener, 2019; Passchier & Sürmelihindi, 2019; Sürmelihindi, Passchier, Baykan, et al, 2013; Sürmelihindi et al, 2021). However, exceptions exist such as the gently sloping arcade of the Anio Novus aqueduct of Rome which was documented to have dense and coarse crystalline carbonate (Carrara & Persia, 2001; Motta, et al, 2015, 2022).…”
Section: Properties Of Carbonate Deposits In Water Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In aqueduct channel sections that are steep and where no daylight penetrates, deposits are usually sparitic and dense due to fast water flow and reduced biological activity, while gently dipping sections, with slow water flow or sections where light is admitted to the channel, tend to be dominated by more micritic and porous deposits (Figures 2a‐X,XI, 4e and 5d) (Kessener, 2019; Passchier & Sürmelihindi, 2019; Sürmelihindi, Passchier, Baykan, et al, 2013; Sürmelihindi et al, 2021). However, exceptions exist such as the gently sloping arcade of the Anio Novus aqueduct of Rome which was documented to have dense and coarse crystalline carbonate (Carrara & Persia, 2001; Motta, et al, 2015, 2022).…”
Section: Properties Of Carbonate Deposits In Water Systemsmentioning
confidence: 99%
“…Such porous micrite may contain small branching structures known as travertine shrubs (Sivaguru et al, 2022). Favourable conditions for the development and persistence of biofilms are found in slow‐flowing water, in water with a high detrital load; and where light is admitted to the channel (Figures 2‐X,XI, 4e and 5d) (Kessener, 2019; Sürmelihindi, Passchier, Baykan, et al, 2013; Sürmelihindi et al, 2018, 2021). Cyanobacteria produce extracellular polymeric substances (EPS) that can promote micrite nucleation (Emeis et al, 1987; Kandianis et al, 2008; Pedley et al, 2009; Riding, 2000; Rogerson et al, 2008).…”
Section: Properties Of Carbonate Deposits In Water Systemsmentioning
confidence: 99%
“…Many of these canals and aqueducts carried spring waters and retain mineral deposits that can be used to better understand their operational history. For example, Surmelihindi et al (2021) analyzed carbonate deposits from the main aqueduct system of the Byzantine capital of Constantinople. Stable isotopes, trace elements, and thin‐section analyses from different sections of the system provided insights into water chemistry and use history, which, in turn, combined with historical records, provided a more accurate picture of water use in historical urban centers.…”
Section: Domestic Consumption and Ritualmentioning
confidence: 99%
“…An estimate of the earthquake size was not given by the authors; however, assuming 0.35 m as the maximum coseismic displacement, the model by Wells and Coppersmith (1994) predicts a shallow earthquake of magnitude of M W 6.3. Sürmelihindi et al (2021) did a detailed study of the carbonates from the 4th and 5th century AD aqueduct system of Constantinople which at a length of 426 km was the longest known water supply system of the ancient world. As the carbonate thickness covers less than 27 years of operation, they could deduce that the aqueduct was thoroughly maintained over the historically documented period of operation over at least 700 years.…”
Section: Aqueducts In Archaeoseismologymentioning
confidence: 99%
“…Previous studies (e.g. Passchier et al 2013;Sürmelihindi et al 2021) have shown that tufa deposits can be helpful to uncover the history of aqueducts as they record the periods of active operation and can be physically dated. Sections A, C, and E show calcite (tufa) accumulation in several places where water spilled down the sides of the aqueduct (Fig.…”
Section: Tufa Deposits and Spillingmentioning
confidence: 99%